READING SCORES AND GENDER - Waxman, Geffrey (European Scientific Journal, ESJ, 2015)
This research investigated fourth-grade reading scores and gender. The study used data from a population of 156,590 fourth graders taking the 2011 NAEP reading test to determine variables and factors affecting reading scores on the general student, male, and female populations. Variables were chosen based on the literature and researcher’s preference. These variables included economic status, race, school variables, student variables, and teacher variables. Using principal component factor analyses orthogonal factors were derived from Varimax factor loading. Correlations and multiple regression analyses were performed on all variables and factors using standardized and unstandardized data. Split data for male and female students were analyzed. Significant results (p < .001) were found for most items and most factors indicating that females did significantly better on the fourth-grade reading test than males. Furthermore, the research indicated that home resources, outside school reading experiences, liking to read, and economic status probably had the greatest influence on fourth-grade reading scores